Propeties of H alpha emitters at z ∼ 2.3: Derivation of H alpha luminosity from multi-band photometry. Issue Volume 15:Issue S341(2019) (November 2019) - Terao, Yasunori; Spitler, Lee; Motohara, Kentaro
Abstract: The measurement of Hα luminosity for large numbers of galaxies is important to investigate recent star formation history of galaxies. With SED fitting that includes emission line templates, we extract individual galaxy Hα luminosities from broad-band photometry. We compare Hα luminosity function with the result of a narrow-band survey, HiZELS, and find there are more luminous galaxies in Hα than previously reported. As a result, our derived star formation rate density at z ∼ 2.3 turns out to be 2.2 times higher than previous studies. Most of the offset in the results can be explained by missing Hα in the HiZELS photometric aperture and different methods for dust extinction correction.